Qualitative and quantitative characteristics of black patch trait in Oujiang color common carp - Ke Jing; Huifan Chen; Nusrat Hasan Kanika; Penghui Zhang; Roland Nathan Mandal; Chunxiao Zeng; Zhiyi Zhang; Jun Wang; Chenghui Wang (Aquaculture Reports)
The black patches in Oujiang color common carp (Cyprinus carpio var. color) encompasses both the formation of patches and their intricate color distribution, and has been considered as the qualitative trait. Using the crossing families of the two kinds of body color patterns in this carp, ''RB'' (red with big black patches) and ''WW'' (white body), we found Mendel's laws of inheritance patterns of black patches in Oujiang color common carp, suggesting the black patches would be controlled by single dominant gene and looked as a qualitative trait. The coverage ratio of the black patches (CRB) in the hybrid was found continuous and nearly normal distribution. Compared with the parent RB, the sizes of melanocytes were significantly smaller, but the number of melanocytes was significantly higher in the hybrid. The melanin layer under the epidermis (Ep) in the hybrid was nearly one-half of that in the parent RB. The melanin content and tyrosinase activity, melanin metabolic enzyme activity of the skin in the hybrid were in the middle between the parents RB and WW. Furthermore, the six relative gene expression levels of the melanogenesis pathway, Ednrb, Tyr, Tyrp1, Mc1r, Kit and Asip, in the skin of the hybrid were between the parent RB and WW. These results demonstrated that the black patches exhibits quantitative traits in nature. Gene editing on Ednrb by using the CRISPR/Cas9 system showed that the mutants displayed a significantly reduced number of black patches in comparison to the wild-type RB, accompanied by noticeably smaller melanocytes. Generally, our study uncovers the dual nature of the black patches: the presence of black patches is categorized as a qualitative trait, whereas the number of black patches is classified as a quantitative trait.